Visual recovery in a patient with optic neuropathy secondary to copper deficiency - Arman Mosenia; Soman Khan; Moe H. Aung (American Journal of Ophthalmology Case Reports)
Purpose: To highlight the utility of ganglion cell layer (GCL) analysis in early diagnosis of optic neuropathy secondary to copper deficiency and emphasize the importance of timely repletion for visual recovery. Observations: A 67-year-old woman presented with four months of gradually decreasing vision bilaterally. Medical history was significant for Stage I duodenal and Stage III colon cancer treated with Whipple surgery and hemicolectomy. Her visual acuity at presentation was counting-fingers vision in both eyes (OU). No relative afferent pupillary defect was noted. Fundus exam revealed a questionable trace temporal optic disc pallor with symmetric cup-to-disk ratio of 0.4 OU. Intraocular pressures were within normal limits OU. On initial optical coherence tomography (OCT) analysis, retinal nerve fiber layer (RNFL) measurements were normal OU; however, GCL loss was noted in both eyes, left eye (OS) being worse than right eye (OD). On subsequent formal visual field testing, she had cecocentral scotoma and large nasal step in both eyes, again worse in OS. Laboratory investigations revealed a significantly depleted copper level at less than 500 μg per liter (normal limit of 810–1990), while levels of B1 (thiamine), B9 (folic acid), and B12 (cobalamin) levels were within normal limits. She was started on oral copper supplementation. At 2-year follow-up, her best corrected visual acuity improved to 20/25 OD and 20/40 OS while maintained on oral copper repletion. Conclusions and importance: Optic neuropathy secondary to copper deficiency is a rare but treatable cause of vision loss. In early stages of disease, early GCL loss may precede changes in the RNFL thickness or even appearance of obvious disc pallor on fundus exam. Visual recovery post repletion may be favorable if detected in a timely fashion.